Pengaruh Model Pembelajaran Inquiri Terbimbing Berbantuan Video Terhadap Sikap Ilmiah Dan Hasil Belajar Pada Konsep Usaha Dan Energi - Dewi Belinda; Tya Ayu Palupy (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This study aims to determine the effect of video-assisted guided inquiry learning model on scientific attitudes and learning outcomes in the concept of work and energy. This research was conducted by FKIP Elementary School Teacher Education Study Program, Pohuwato University in the 2024/2025 academic year with a sample of 50 students, consisting of 25 students in the experimental class and 25 people in the replication class. This study uses the method This study uses a "one groups pretest-posttest design" design, where a pretest will be given before and a posttest will be given after treatment is given. This design uses one experimental class and one replication class. The data collection technique was carried out through purposive sampling, and the instrument used was an essay test consisting of 13 questions consisting of C1, C2, C3 and C4 and 40 statement items representing 15 indicators of scientific attitudes. The answers to the test results and questionnaires were analyzed using SPSS software version 22 with the Independent Sample Test. The results of the hypothesis test showed a sig value (2-tailed) of 0.000. Because the sig value (2-tailed) <0.05, the null hypothesis is rejected and the alternative hypothesis is accepted. This shows a significant effect of the video-assisted guided inquiry learning model on students' scientific attitudes and creative thinking skills in physics learning. The N-Gain analysis of learning outcomes showed that the experimental class achieved values ​​​​of 0.84 and 0.82 which are included in the high category. These results indicate that learning using the guided inquiry model can improve students' scientific attitudes and creative thinking skills.